2020
DOI: 10.1108/el-06-2020-0130
|View full text |Cite
|
Sign up to set email alerts
|

Predicting the future increment of review helpfulness: an empirical study based on a two-wave data set

Abstract: Purpose Identifying and predicting the most helpful reviews has been a focal interest in the fields including information management, e-commerce and marketing, etc. Though many factors are found correlated to the helpfulness of reviews, they may suffer endogeneity problems, as normally the data is observed in the same time window. This paper aims to tackle such a problem by examining the predictive power of different factors on the future increment of review helpfulness. Design/methodology/approach Adopting … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 38 publications
1
3
0
Order By: Relevance
“…(2) Review replies, review depth, review pictures, positive reviews and review time have been highlighted over the past decade as common review-level factors that correlate with review usefulness (Pan et al, 2021). The meta-analysis in this study also confirmed a significant relationship between the above aforementioned factors and perceived usefulness, but the degree of correlation differed.…”
Section: Discussion Of Findingssupporting
confidence: 65%
See 2 more Smart Citations
“…(2) Review replies, review depth, review pictures, positive reviews and review time have been highlighted over the past decade as common review-level factors that correlate with review usefulness (Pan et al, 2021). The meta-analysis in this study also confirmed a significant relationship between the above aforementioned factors and perceived usefulness, but the degree of correlation differed.…”
Section: Discussion Of Findingssupporting
confidence: 65%
“…(1) Existing studies have mainly focused on the impact of reviewer characteristics and review contents on review usefulness. Insufficient attention has been paid to the impact of the review reader's characteristics (Pan et al, 2021). People with a high tendency to trust are more willing to trust strangers, and the existing literature also verifies that whether consumers are willing to trust online reviews depends on trust tendency (Filieri, 2015;Luo and Li, 2013).…”
Section: Discussion Of Findingsmentioning
confidence: 99%
See 1 more Smart Citation
“…As shown in Figure 1, we regard the round 12 data as the historical records, from which the reviewer features are extracted, including especially the experience distribution. Inspired by the framework proposed by Pan et al (2021), the reviews posted between t1 and 14 September 2018 (t) are the target reviews for the latter econometric analysis. The helpfulness of the target reviews, i.e.…”
Section: Data Collection and Research Methodologymentioning
confidence: 99%